Liberty or Death: An Analysis of the Relationship Between Decolonization and Post-Colonial Insecurity in Lusophone Africa - Rio Tinto, D. (Annual Convention of the International Studies Association (ISA), 2018)
In this paper, I examine the relationship between the late decolonisation process triggered by the 1974 Carnation Revolution in Portugal and the domestic insecurity experienced in the now former colonies in Lusophone Africa. To do so, I employ an exhaustive comparative approach, looking at the conditions informing different outcomes in every country within Lusophone Africa: Angola, Cape Verde, Guinea-Bissau, Mozambique and S. Tomé e Princípe. I argue that the existing historiography of the cases favours explanations based on predatory behaviour (greed) by the new elites in the colonies, to the detriment of explanations looking at the insecurity experienced by those agents. Importantly, this research suggests that the outcome of post-colonial violence in post-colonial Lusophone Africa has varied in accordance with the experience of extreme insecurity rather than with the presence of greedy actors, as well as the effect of state capacity. Furthermore, the dynamics through which state capacity and insecurity impact on the outcome of post-colonial violence are further related to the quality of attempts at political settlements, the barriers to the mobilisation of violence and the role of the former colonial power in assisting the transition.